Hubungan Perilaku Mengkonsumsi Makanan Siap Saji (Fast Food) dengan Kejadian Dismenorea pada Remaja: Literature Review - Rizky Dwi Falafiya Putri; Rizka Etsy Safriana (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Dysmenorrhea is one of the most common gynecological complaints experienced by adolescent girls and can affect the quality of life and daily activities. Various risk factors for dysmenorrhea have been identified, including lifestyle factors and dietary patterns. One dietary pattern that is often associated with an increased risk of dysmenorrhea is the consumption of fast food among adolescents. Based on a review of several observational and experimental studies, it was found that adolescents who often consume fast food tend to have a higher risk of experiencing dysmenorrhea, both in terms of frequency and severity. The imbalanced nutritional content in fast food is suspected to contribute to increased inflammatory processes and uterine contractions, which worsen dysmenorrhea symptoms. Therefore, nutritional interventions and education about healthy eating patterns among adolescents need to be improved as part of prevention efforts.